SEBUAH REFLEKSI : Efektivitas Kerja Pimpinan - Sola, Ermi (Idaarah: Jurnal Manajemen Pendidikan, 2017)
The word effectiveness broadly refers to the ability of an organization in achieving the objectives (outcomes) that have been specified appropriately. Of course, the achievement of these goals can be achieved with and the involvement and collaboration of all members of the organization in carrying out its functions and duties respectively. The right activity or job - doing the right thing - run by every individual in the organization, though heavy, will be solved more easily in a simpler way. No less important the various tasks and activities of the organization must be run by optimizing all resources owned in an effort to achieve organizational goals. An organization can be said to succeed when the established goals can be achieved appropriately.